A database search for hammerhead ribozyme motifs. (1st June 2005) - Gräf, S.; Przybilski, R.; Steger, G.; Hammann, C.
Abstract : The hammerhead ribozyme is the smallest naturally occurring RNA endonuclease. It is found in subviral plant pathogens and transcripts of satellite DNA from a limited number of organisms. We have performed a database search for novel examples of this catalytic RNA, taking into consideration the recently defined structural requirements for an efficient cleavage under physiological magnesium ion concentrations. In this search, we find, apart from the known examples, several hundreds of motifs in organisms of all kingdoms of life. In a first set of experiments, we analysed hammerhead ribozymes from Arabidopsis thaliana . We found that these sequences are tissue-specifically expressed and that they undergo self-cleavage in planta . Furthermore, their activity under physiological magnesium ion concentrations depends on functional loop–loop interactions, as shown by the lack of activity of appropriate mutants.